(untitled) (TEST Ticontre. Theory Text Translation, 2023)
The aim of this paper is to consider the ways and intentions of Milo de Angelis’ translation experience of Lucretius’ De rerum natura. The first part will provide a comparison between the translation of a Lucretian passage, operated by the editorial board of «Niebo», quarterly journal of poetry led by De Angelis for three years, and a later version of the same passage operated by De Angelis alone. This will highlight the shift between a translation that remains completely faithful to the ancient author and one that operates more freely. In the second part, the paper will consider the progression of De Angelis’ lecture of De rerum natura, by analyzing some passages from the Lucretius’ anthological collection, Sotto la scure silenziosa (SE 2005), and by showing the evolution of translation toward a proper ‘rewriting’. In questo lavoro sono indagate le modalità e le intenzioni dell’esperienza traduttiva di Milo De Angelis intorno al De rerum natura di Lucrezio. Nella prima parte della ricerca si proporrà il confronto tra un brano lucreziano tradotto dalla redazione di «Niebo», rivista quadrimestrale di poesia, diretta per tre anni da De Angelis, con una traduzione successiva ad opera del solo De Angelis, mettendo in luce l’evoluzione da una resa complessivamente fedele all’autore antico ad una resa più libera. Nella seconda parte, il lavoro considererà lo sviluppo della lettura deangelisiana del De rerum natura, analizzando alcuni brani tratti dalla raccolta antologica lucreziana Sotto la scure silenziosa (SE 2005) e mostrando l’approdo ad una traduzione che si presenta nella forma di una riscrittura vera e propria.